PELATIHAN PEMBUATAN MEDIA AJAR DAN SIMULASI UJIAN ANBK BERBASIS DARING - Vittalis Ayu; Bambang Soelistijanto; Henricus Agung Hernawan; J.B. Budi Darmawan; Bernadeta Wuri Harini; Martanto Martanto (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The education sector is one of the most impacted areas of the COVID-19 pandemic. Schools, which generally hold offline meetings, now have to transform into online sessions. With this pandemic, the teaching process must be "forced" to be online. The assignment model is usually given in physical mode (questions on paper, done and collected) is no longer relevant because of the limitations of physical meetings. On the other hand, students need an explanation from the teacher directly because they are familiar with the context of offline learning. Judging from the lack of computer ownership, whether owned by students or their parents, the technological literacy of the student and the teacher is required to carry out this teaching and learning process properly. To answer this problem, the Informatics and Electrical Study Program at Sanata Dharma University held training activities for making teaching media for SD Negeri Sawah teachers, who ultimately played an important role in improving teachers' technological literacy in carrying out online learning. In addition, at the school's request, we also held a phase 2 training targeting fourth-graders in preparation for the ANBK, a computer-based national exam they had to pass in the following year, which successfully increased the student's confidence to sit the test.